Development of Planning in Children with High‐Functioning Autism Spectrum Disorders and/or Attention Deficit/Hyperactivity Disorder. Issue 7 (7th October 2015) - Unterrainer, Josef M.; Rauh, Reinhold; Rahm, Benjamin; Hardt, Jochen; Kaller, Christoph P.; Klein, Christoph; Paschke‐Müller, Mirjam; Biscaldi, Monica
Abstract : Planning impairment is often observed in children with high‐functioning autism spectrum disorders (ASD), but attempts to differentiate planning in ASD from children with attention deficit hyperactivity disorder (ADHD) and typically developing children (TD) have yielded inconsistent results. This study examined differences between these groups by focusing on development and analyzing performance in searching ahead several steps ("search depth") in addition to commonly used global performance measures in planning. A cross‐sectional consecutive sample of 83 male patients (6–13 years), subgrouped as ASD without (ASD−, n = 18) or with comorbid ADHD (ASD+, n = 23), ADHD only ( n = 42) and n = 42 TD children (6–13 years) were tested with the Tower‐of‐London‐task. For global performance, ASD+ showed the lowest accuracy in younger children, but similar performance as TD at older ages, suggesting delayed development. Typically, a prolongation of planning time with increasing problem difficulty is observed in older children as compared to younger children. Here, this was most pronounced in ASD−, but under‐expressed in ADHD. In contrast to global performance, effects of search depth were independent of age. ASD−, but not ASD+, showed increased susceptibility to raised demands on mentally searching ahead, along with the longest planning times. Thus, examining both global and search depth performance across ages revealed discernible patterns of planning between groups. Notably, the potentially detrimental impact of two diagnosed disorders does not add up in ASD+ in this task. Rather, our results suggest paradoxical enhancement of performance, ostensibly attributable to disruption of behavioral rigidity through increased impulsivity, which did not take place in ASD−. Autism Res 2016, 9: 739–751 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.